INTENSI MENIKAH PADA MAHASISWA DI MASA PANDEMI COVID-19 - Mustary Emilia; Farwan Farwan; Sukmawati Sukmawati; Era Fasira (Institut Agama Islam Negeri (IAIN) Manado, 2021)
ABSTRACTThis study aims to examine and describe the marriage intention in college students during the COVID-19 pandemic based on the theory of planned behavior from Ajzen (2005) with three determinant factors, namely attitude toward behavior, subjective norm, and perceived behavioral control. This study used a qualitative approach with data collection in the form of interviews with primary data sources. The subjects in this study amounted to 3 female students with the criteria for will getting married and had got engaged. The data analysis technique was carried out using an interactive analysis model by Miles and Huberman, namely data collection, data reduction, data presentation/display, then conclusions or verification. The results showed that the Covid-19 pandemic did not affect the students' marriage intention. Determinants of marriage intentions are formed from attitudes towards the behavior in the form of a positive attitude towards marriage which is obtained from the belief in the positive benefits that are imagined and the description of the risks that will be faced. The next marriage intention is formed by subjective norms in the form of parental influence and the desire to imitate the positive experiences of other students who are married while studying. Furthermore, the intention to marry is formed on the determinants of perceived behavioral control factors in the form of the subject's belief in the ability to control behavior to prevent conflict and find solutions to household problems that will be faced stemming from his status as a student. Another finding in this study is that belief in religion and adherence to religious teachings are sources of information that strengthen the determinant factors so as to form a strong intention to marry.Keywords: intention, marriage, college students, covid-19ABSTRAKPenelitian ini bertujuan untuk mengkaji dan mendeskripsikan intensi menikah pada mahasiswa di masa pandemi covid-19 berdasarkan teori perencanaan perilaku dari Ajzen (2005) dengan tiga faktor determinan yaitu attitude toward behavior, subjective norm, dan perceived behavioral control. Penelitian ini menggunakan pendekatan kualitatif dengan pengambilan data berupa wawancara pada sumber data primer. Subjek pada penelitian ini berjumlah 3 orang mahasiswi dengan kriteria akan melangsungkan pernikahan dan telah menjalani proses lamaran. Teknik analisis data dilakukan dengan model analisis interaktif oleh Miles dan Huberman yaitu pengumpulan data, reduksi data, presentasi/display data, lalu kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa pandemi covoid-19 tidak mempengaruhi intensi menikah pada mahasiswa. Determinan intensi menikah dibentuk dari sikap terhadap perilaku (attitude towards the behavior) berupa sikap positif terhadap pernikahan yang didapatkan dari keyakinan akan manfaat positif yang dibayangkan serta gambaran resiko yang akan dihadapi. Intensi menikah berikutnya dibentuk oleh norma subjektif (subjective norm) berupa pengaruh orangtua serta keinginan untuk meniru pengalaman positif mahasiswa lain yang menikah sambil kuliah. Selanjutnya, intensi menikah dibentuk atas determinan faktor persepsi kontrol perilaku (perceived behavioral control) berupa keyakinan subjek akan kemampuan mengontrol perilaku untuk mencegah konflik maupun menemukan solusi dalam permasalahan rumah tangga yang akan dihadapi yang bersumber dari statusnya sebagai mahasiswa. Temuan lain dalam penelitian ini adalah keyakinan terhadap agama serta kepatuhan terhadap ajaran agama menjadi sumber informasi yang memperkuat faktor determinan sehingga membentuk intensi yang kuat untuk menikah. Kata Kunci: Intensi, mahasiswa, menikah, covid-19.